Prophylactic Antibiotics in Twin Pregnancies Complicated by Previable Preterm Premature Rupture of Membranes - Myrick, Olivia; Dotters-Katz, Sarah; Grace, Matthew; Manuck, Tracy; Boggess, Kim; Goodnight, William (American Journal of Perinatology Reports, 2016)
Objective This study aims to determine if antibiotics given for latency to women with twins and previable preterm premature rupture of membranes (PPROM) affect the duration from membrane rupture to delivery.Methods A retrospective cohort study of twin pregnancies at a single center from 2000 to 2015 with previable (14 0/7–22 6/7 weeks) PPROM was conducted. Women who were not candidates for expectant management or who elected for immediate delivery were excluded. Pregnancy complications, delivery data, and neonatal outcomes were compared between women who did and did not receive latency antibiotics. The primary outcome was latency.Results Of 52 eligible women, 30 (64%) elected expectant management; 17 women received antibiotics and 13 did not. No demographic differences existed between the groups. The median gestational age of rupture was 20 and 20.3 weeks in the antibiotic group and no antibiotic group, respectively. Median latency was 0.8 and 2.4 weeks in the antibiotic and no antibiotic groups correspondingly (p = 0.21). Overall, 58.8 and 23.1% of women who did and didn't receive antibiotics developed chorioamnionitis (p = 0.07). Perinatal mortality and maternal complication rates were high, though not different between the groups.Conclusion Currently, even though in singletons with previable PPROM there is a recommendation to consider administrating antibiotics, in the setting of twins, no evidence exists to support this.
Keywords: multiple gestation; PPROM; previable preterm premature rupture of membranes; twins